2019
DOI: 10.1007/s40618-019-01164-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers for the classification of cytologically indeterminate thyroid nodules

Abstract: Background The diagnosis of indeterminate lesions of the thyroid is a challenge in cytopathology practice. Indeed, up to 30% of cases lack the morphological features needed to provide definitive classification. Molecular tests have been developed to assist in the diagnosis of these indeterminate cases. The first studies dealing with the preoperative molecular evaluation of FNA samples focused on the analysis of BRAF V600E or on the combined evaluation of two or three genetic alterations. The sensitivity of mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 120 publications
1
32
0
1
Order By: Relevance
“…An increasing number of studies have concluded that molecular testing of thyroid nodules has a significant diagnostic as well as prognostic value and can help improve management of patients. [19][20][21][22][23][24][25] Other studies, however, question the clinical utility and costbenefit analysis of molecular testing. [20,24] The Afirma Gene Expression Classifier (Afirma®, Veracyte, Inc., South San Francisco, CA) measures mRNA transcript levels of 142 genes and has shown to have a high sensitivity of 91% and a moderate specificity of 68%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have concluded that molecular testing of thyroid nodules has a significant diagnostic as well as prognostic value and can help improve management of patients. [19][20][21][22][23][24][25] Other studies, however, question the clinical utility and costbenefit analysis of molecular testing. [20,24] The Afirma Gene Expression Classifier (Afirma®, Veracyte, Inc., South San Francisco, CA) measures mRNA transcript levels of 142 genes and has shown to have a high sensitivity of 91% and a moderate specificity of 68%.…”
Section: Discussionmentioning
confidence: 99%
“…[20,24] The Afirma Gene Expression Classifier (Afirma®, Veracyte, Inc., South San Francisco, CA) measures mRNA transcript levels of 142 genes and has shown to have a high sensitivity of 91% and a moderate specificity of 68%. [18,22] ThyGeNEXT (ThyGeNEXT®, Interpace Diagnostics, PDI Inc, Parsippany, NJ) and ThyroSeq v3 (ThyroSeq® joint partnership between UPMC and CBLPath, Pittsburgh, PA) are two comprehensive tests, designed to improve the overall accuracy of molecular testing, with sensitivity of 89% and 94% and specificity of 85% and 82%, respectively. [20,24] The data regarding the clinical utility of molecular testing in patients with a Bethesda V and VI thyroid nodules remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of MT is based on performance factors such as specificity, sensitivity, PPV, Negative predictive value (NPV), and prevalence. It should either provide the information if a test can "rule out" cancer (likelihood that a nodule is benign) and reduce diagnostic surgery for benign nodules or "rule in" cancer (likelihood that the nodule is malignant) to optimize extent of surgical treatment [82,117]. Therefore, high sensitivity and NPV would be ideal to "rule out" malignancy, while high specificity and high PPV would help to "rule in" malignancies [148].…”
Section: Proteome Based Markersmentioning
confidence: 99%
“…The availability of molecular markers enhanced was significantly increased by the advent of next generation sequencing technology, and the gene expression classifier has also added a valuable contribution in the diagnosis of thyroid nodules ( 8 , 9 ). However, these tools are not routinely used in Europe because of the high cost ( 10 ). Recently, the availability of high-frequency ultrasonography and the development of risk scores that can quantify the risk of malignancy have significantly implemented the decision-making in the thyroid nodules ( 11 ).…”
Section: Introductionmentioning
confidence: 99%